Workflow optimization in engineering document management using MTC digital transmittal system. - Kamaruzaman, Khairul Amin; Mohamad Rosman, Mohamad Rahimi; Hairai, Ummu Sakinah (International Journal of Accounting, Finance and Business, 2026)
Document transmittal plays a critical role in engineering projects, ensuring that drawings and technical documents are formally submitted and reviewed. However, many organizations still rely on email and shared folders, leading to revision confusion, scattered records, delayed approvals, and limited traceability. To address these issues, this project develops the MTC Engineering Transmittal System, a web-based platform that centralizes document submission and approval workflows. The system supports file upload, revision tracking, QC checking, approval routing, audit logging, and reporting, with clearly defined user roles. Developed using a structured methodology and supported by system modelling and testing, the platform enhances document visibility, reduces approval delays, and improves accountability in engineering document control processes